BUDAYA NASIONAL DI TENGAH PASAR: KONSTRUKSI, DEKONSTRUKSI, DAN REKONSTRUKSI - Setiawan, Ikwan (Sekolah Pascasarjana UGM, 2012)
In the Reformation period, the state regime still mobilizes traditional-ideal values as national culturewithout giving conceptual and operational explanations. In this article, I combine two approaches,cultural studies and postcolonial studies, for reading national culture as represented in some PresidentSoesilo Bambang Yudhoyonoâs presidential speeches. I will analyze ideal-but-ambivalent constructionsof national culture in regimeâs perspective as represented in those speeches, particularly, in the contextof continuous of national culture in regimeâs perspective in those speeches, particularly, in the context ofthe governmentâs continuous mobilization of traditional meanings as the invisible power for Indonesianpeople, while, at the same time,placing emphasis on economic progress.Instead of a strategic culturalconstruction, national culture produces its own deconstruction and fails to be discursive formation.Further, I argue that the regime operates their governmentality by reconstructing newer nationalculture based on market economics as discursive constructions, which ideally can provide conceptualand material basis for state regime in conducting governance and for citizens in achieving welfare inneoliberal formation.